Leptin contributes to the taxol chemoresistance in epithelial ovarian cancer - Gu, Fei (Oncol Lett, 2019)
Epithelial ovarian cancer (EOC) is a gynecological malignancy with high morbidity. Treating EOC remains a challenge, as the pathogenesis of this disease remains unclear and chemoresistance is a common occurrence. A number of previous studies have revealed that obesity is closely associated with cancer and leptin, as a link between cancer and obesity, has become a focus of research in recent years. In the present study, survival database analysis demonstrated that leptin expression was associated with poor prognoses in patients treated with platinum and paclitaxel/docetaxel. A cell activity assay demonstrated that leptin reduced the chemosensitivity of ovarian cancer cells to paclitaxel/docetaxel. Furthermore, flow cytometry results revealed that treatment with exogenous leptin reduced the proportion of ovarian cancer cells in G2/M phase, which was significantly elevated following paclitaxel/docetaxel chemotherapy. It was also verified that transcription factor CCAAT/Enhancer Binding Protein α can bind to the upstream promoter region of leptin and activate its transcription in ovarian cancer cells. Together, these results suggest that leptin serves an important role in chemoresistance and may serve as a novel therapeutic target for ovarian cancer in patients treated with platinum and paclitaxel chemotherapy.